Assessing the Outcomes of Digital Soil Science Curricula for Agricultural Undergraduates in the Global South - Rico Heidy; de la Puente Mario; de Oro Carlos; Navarro Daniela; Lambis Juan; Londoño Guillermo (Open Education Studies)
This academic inquiry examines the efficacy of virtual reality (VR)-based pedagogy for higher learning, specifically analyzing immersive digital instruction for rural agriculture undergraduates studying soil science in Colombia. The investigation tests two hypotheses: first, simulated learning situations improve academic achievement and student investment compared to conventional in-person lectures; and second, modern modalities cultivate affirmative perspectives of the material. Employing a meticulous investigative blueprint across three Colombian university campuses situated in pastoral communities, the assessment involved 89 volunteers separated into experimental and control groups over 14 weeks analyzing soil nutrient administration. Scholastic aptitude, student absorption, and viewpoint appraisals were conducted before and after the module. Statistical calculations including independent sample examinations, variance examinations, effect magnitude, and association analyses were utilized to validate the hypotheses. The results endorse both hypotheses, evidencing augmented academic performance, student engagement, and affirmative attitudes toward soil science among participants experiencing VR-based coursework. This inspection lends valuable discernment into advanced technology’s potential to address rural student challenges, elevating educational outcomes and furthering constructive pedagogical encounters in the developing world.